IMPROVING THE METHODOLOGY OF USING MOBILE GAMES TO IMPROVE THE TRAINING EFFICIENCY OF YOUNG VOLLEYBALL PLAYERS - Ramazonova Zarina Sodiq qizi (TADQIQOTLAR, 2025)
Abstract: a comprehensive review of the methodology of using motion studies to improve the training of young volleyball player. After tea To the physical development of volleyball in the spirit of making a team and product, shorts recommending games and fast action team. By the individuality of each athlete after your pay grade to learning and new learning techniques for coaches, and sharing your experiences, were reported in the potential of young athletes can be enhanced. The highway encourage proposals from the volleyball player to be active and successful.